2021
DOI: 10.3390/ma14195697
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Dry Routing of CFRP Composite: Temperature, Forces, Tool Wear, and Fine Dust Emission

Abstract: This article presents the influence of machining conditions on typical process performance indicators, namely cutting force, specific cutting energy, cutting temperature, tool wear, and fine dust emission during dry milling of CFRPs. The main goal is to determine the machining process window for obtaining quality parts with acceptable tool performance and limited dust emission. For achieving this, the cutting temperature was examined using analytical and empirical models, and systematic cutting experiments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…Moreover, feed rate has more impact on tool wear than that of cutting speed. This result is consistent with those documented by [26]. However, in the study of [27], the authors showed that cutting speed has a stronger impact on tool wear compared with those feed rates because cutting speed is the major factor influencing cutting temperatures.…”
Section: Introductionsupporting
confidence: 90%
“…Moreover, feed rate has more impact on tool wear than that of cutting speed. This result is consistent with those documented by [26]. However, in the study of [27], the authors showed that cutting speed has a stronger impact on tool wear compared with those feed rates because cutting speed is the major factor influencing cutting temperatures.…”
Section: Introductionsupporting
confidence: 90%
“…They found that surface roughness (Ra) increased with increasing feed rate and decreased with increasing cutting speed. In contrast, different results were found by Elgnemi et al 23 in which the cutting force and tool wear increased as the cutting speed increased from 100 m/min to 200 m/min during the dry milling of CFRP with carbide milling cutters. Nor Khairusshima et al 24 studied the tool wear of a carbide milling cutter and found that the tool wear rate increased with increasing cutting speed and feed rate.…”
Section: Introductionmentioning
confidence: 67%
“…In CFRP, the fibers bear the load while the resin facilitates force transfer between the fibers. Therefore, the failure modes of the material can be analyzed primarily based on the stresses experienced by the fibers [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%